User response of learning application Arabic language - Muhammad Amiruddin (International Journal of Language and Ubiquitous Learning, 2023)
Background. Accelerating the mastery of a second language is a challenge for the majority of students and academics. Interactive applications for learning foreign languages that look attractive, the material is appropriate, easy aka practical, muted and accelerative are certainly very much needed and sought after. I have distributed and researched this Arabee application made in Turkish during arabic learning at the Ulul Albab campus of Universitas Islam Negeri Malang. Purpose. This study aims to introduce and see the response to the Arabee Arabic language learning application. Method. The data collection method used by researchers is dominated by questionnaires. This research was structured with qualitative methods. The research sample was taken from various students of Islamic Universities and Arabic language activists in the country. Results. The results of this study indicate that the performance of the arabee application (alifbee now) is so captivating. The systematic learning topics raised in this application are appropriate and closely related to current trends. The use of this application is easy to operate. It is hoped that this application can appear in the future in the Indonesian-Arabic version. Conclusion. The appearance of the arabee or alifbee application has captured many hearts, especially campus academics at the university / institute level in Indonesia. The systematic learning topics raised in this application, judging from the respondents' input, have a good level of suitability and relevance and or are very related to current trends and life.